Gels: formation, structure and utilization in crystal growth - Demadis, Konstantinos D. (My University, 2015)
Gels are ubiquitous in Nature and everyday life. This presentation will focus on the utilization of gels in the art of crystal growing. Several scientific disciplines depend on formation and characterization of crystals. Numerous times to obtain a single crystal is necessary for full identification of a new compound or a pharmaceutical ingredient. Specific cases will be presented on the successful use of gel systems in crystal growth.
Keywords: Coloides; Crystal growth; Gel; Structure; Synthesis